Evaluation of various symptoms in subjects with mass in right iliac fossa - K. S., Balasubrahmanya; Pawar, Praveen M.; M., Srinidhi; K. V., Jinumon; S., Shruthi; Tanga, Vishal (International Surgery Journal, 2017)
Background:Mass in right iliac fossa is a very common condition a surgeon will come across in day to day practise. This study was aimed at assessing various symptoms with which subjects with mass in right iliac fossa present to clinician. Methods: 50 eligible subjects admitted in K. R. Hospital who were diagnosed to have mass in right iliac fossa clinically or radiologically were selected after informed valid consent. A proper history, thorough clinical examination and relevant investigations were done to diagnose the pathology. Various symptoms were assessed. Results:In our study, the various conditions which presented as mass in right iliac fossa were appendicular mass (42%), appendicular abscess (16%), ileocaecal tuberculosis (24%), carcinoma caecum (14%), ileopsoas abscess (4%). Various symptoms with which subjects presented were pain abdomen (88%), fever (78%), vomiting (30%), mass per abdomen (28%), weight loss (38%), bleeding per rectum (12%) and bowel disturbances (16%). Appendicular pathology was most common cause in younger age group and carcinoma caecum and ileocaecal TB was more prevalent in older age group. Conclusions:Various symptoms with which subjects presented were pain abdomen, fever, vomiting, mass per abdomen, weight loss, bleeding per rectum and bowel disturbances. Pain abdomen was the most common symptom in subjects with mass in right iliac fossa. Mass per abdomen as a symptom was found in 28% of the subjects.